2014
DOI: 10.1038/ki.2013.457
|View full text |Cite
|
Sign up to set email alerts
|

B cells display an abnormal distribution and an impaired suppressive function in patients with chronic antibody–mediated rejection

Abstract: In kidney transplantation, the composition of the B-cell compartment is increasingly identified as an important determinant for graft outcome. Whereas naive and transitional B cells have been associated with long-term allograft survival and operational tolerance, memory B cells have been linked to graft rejection and graft loss. Chronic antibody-mediated rejection now represents a major complication in transplantation and is a challenge in current therapeutics. Here, we show that patients with chronic antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 26 publications
(31 reference statements)
5
40
0
Order By: Relevance
“…B cells with regulatory properties are of increasing interest in kidney transplantation, in particular clinical outcomes and phenotypes associated with transitional B cells characterized by surface CD19þCD24hiCD38hi expression (5)(6)(7)(8)(9)(10). This study shows that increased frequencies of these transitional B cells are associated with protection from episodes of BPAR in unselected low/medium immune risk transplant recipients followed longitudinally from the time of transplantation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…B cells with regulatory properties are of increasing interest in kidney transplantation, in particular clinical outcomes and phenotypes associated with transitional B cells characterized by surface CD19þCD24hiCD38hi expression (5)(6)(7)(8)(9)(10). This study shows that increased frequencies of these transitional B cells are associated with protection from episodes of BPAR in unselected low/medium immune risk transplant recipients followed longitudinally from the time of transplantation.…”
Section: Discussionmentioning
confidence: 75%
“…In kidney transplantation, the importance of CD19þCD24hiCD38hi cells is highlighted by patients who are ''tolerant'' to their graft, who display increased frequencies of these cells (5)(6)(7)(8), although proof as to their direct role in this phenomenon is lacking. Following these landmark studies, 2 subsequent casecontrol, cross-sectional investigations (9,10) revealed associations between reduced CD19þCD24hiCD38hi frequencies and transplant rejection, albeit mainly in the context of antibody-mediated rejection (ABMR) many years following transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conclusions made are based on indirect evidence of regulation, on depleting specific lymphocyte subsets, rather than a direct demonstration of suppressive activity from purified, and then in vitro assessed cell subpopulations. We presented our flow cytometric analysis of these samples in our earlier article last year, and found no associations between the proportions of B-cell subsets, including transitional or naïve cells and ELISPOT patterns or outcome, 7 although we acknowledge that others working in this field have shown associations between rejection and particular B-cell subsets, including transitional B cells 32, 37, 38. In addition, the associations reported in this article need to be validated in different cohorts of patients, ideally with work to assess the reproducibility of the assays within patients and to more carefully document how patterns change over time.…”
Section: Discussionmentioning
confidence: 93%
“…48 The same observations have been reported in other models. 49 Interestingly, it has been reported that B cells from patients with chronic antibodymediated rejection have a defect in suppressive properties, 50 in contrast with B cells from STAs, which inhibit T cell proliferation and induce Treg generation through a TGF-b-and IDOdependent pathway (personal communication, Nouël et al Ann Rheum Dis abstract A8.32, 2014). In our situation, blocking TGF-b has no effect on the suppressive function of B cells, suggesting that TGF-b is not involved in B cell regulation either.…”
Section: Discussionmentioning
confidence: 99%